Asian Cockroach, Blattella asahinai Mizukubo (Insecta: Blattodea: Blattellidae) - Dina L. Richman (EDIS)
This document is EENY-120 one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2000. Revised: July 2000.